Exposure of tungsten surface to high-flux of helium and argon ions - Bizyukov, I.O.; Girka, O.I.; Starovoitov, R.I.; Bizyukov, O.A.; Bobkov, V.V. (Вопросы атомной науки и техники, 2014)
Present work investigates the erosion yields of tungsten exposed to intense beams of He and Ar ions using weight-loss measurements. The ion beams were generated by FALCON ion source, typical particle fluxes were in the range of (0.4…1.0)×10²²m⁻²•s⁻¹ and the heat fluxes were 0.3…0.8 MW∙m⁻². Investigations show that the erosion yield for He ions is in line with simulations and experimental literature data on physical sputtering, while for Ar bombardment one has observed lower erosion yields. The morphology of the surface has also been studied with SEM.